ATTITUDES TOWARD COVID-19 BOOSTER DOSE VACCINES ACCEPTANCEAMONG HEALTHCARE STUDENTS, KARACHI: A CROSS-SECTIONALANALYSIS - Arif Ali; Benish Zia; Shayan Ali; Ali Ahmed; Naqiha Shabbir (Baqai Journal of Health Sciences)
Objective: This research aims to evaluate the attitude and perception of medical students in Karachi towards Standard Operating Procedures (SOPs) and guidelines for COVID-19 booster dose vaccines.